Arabic-Malayalam Texts at the British Library: Themes, Genres, and Production - Kooriadathodi, Mahmood (International Journal of Islam in Asia, 2022)
By the late nineteenth century, when printing press was popular across the world. In South Asia, there was increased production and dissemination of Tamil and Malayalam vernacular materials in Arabic script. This intermarriage of local languages with a cosmopolitan script was part of a larger trend of the time, and in South India those were advanced by Arabic-Malayalam and Arabic-Tamil literatures (also referred as Malabari and Arwī respectively). Hundreds of texts printed annually at the prime centres of Islamic printing on both Malabar and Coromandel coasts were circulated among mobile and immobile communities of the region across the Indian Ocean, Pacific and Atlantic littorals. The reach and impact of such vernacular printings are yet to be explored thoroughly, for these materials have been spread across several formal and informal collections and there has not been any systematic attempt to identify or catalogue them. In this article, I focus on uncatalogued Arabic-Malayalam materials at the British Library London on which I have been working on in the last few years. These materials from the late-nineteenth and early-twentieth centuries help us understand the history of the region, religion and printing. After a brief historical overview, I focus on some major features, themes, trends, places, and people in about 150 texts I consulted, and which I discuss in relation to broader histories of Arabic-Malayalam tradition.